1995
DOI: 10.1021/j100019a020
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the Spectroscopy and Ultrafast Photochemistry of Chlorine Dioxide

Abstract: Time-resolved spectroscopic techniques are used to examine the photochemistry of OClO in water, alcohol, acetonitrile, toluene, and sulfuric acid solutions. In all solvents, excitation of the near-UV ,A2 -,BI transition leads to two competing photochemical reactions: dissociation into OC1 + 0 and formation of C1 + 0 2 .Based on orbital correlations of the isolated molecule, C1 can be formed by two distinct mechanisms, (1) direct elimination of C1 from OC10, maintianing the GV symmetry axis along the reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 4 publications
1
84
0
Order By: Relevance
“…This slow rise has a time constant of ∼200 ps and has previously been assigned to correspond to the Cl atom radical formation. 40 The transition responsible for this absorption is the Cl-water complex charge transfer transition, which absorbs throughout the wavelength range from 320 to 390 nm. 43,44 In the region of the probe wavelengths from 440 to 700 nm, an absorption initially rises and decays back to zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This slow rise has a time constant of ∼200 ps and has previously been assigned to correspond to the Cl atom radical formation. 40 The transition responsible for this absorption is the Cl-water complex charge transfer transition, which absorbs throughout the wavelength range from 320 to 390 nm. 43,44 In the region of the probe wavelengths from 440 to 700 nm, an absorption initially rises and decays back to zero.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the relative importance of these two channels in aqueous solution. 38,40 Taking advantage of the two distinct electronic states of photoproduct O 2 generated by the two pathways, the relative quantum yield was determined by measuring the phosphorescence emission intensity of O 2 ( 3 Σ g -r 1 ∆ g ) against a known standard. Only about 5% of the Cl radical formed originates from the direct Cl elimination route, indicating that most are generated from the dissociation of the intermediate ClOO.…”
Section: Resultsmentioning
confidence: 99%
“…Recent transient absorption studies of OClO in water provide support for the latter sequence of events. 11,12 Therefore, if C 2V symmetry is maintained during the course of the reaction, direct production of Cl( 2 P u ) + O 2 ( 1 ∆ g ) is possible, but the lowering of symmetry should result in atomic chlorine production via ClOO. The important difference between these pathways is that the C 2V reaction coordinate results in the production of excited molecular oxygen where the C s pathway combined with rapid ClOO internal conversion does not.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,16,[18][19][20]22,25,26,[45][46][47] The minor reaction pathway corresponding to Cl + O 2 formation is believed to proceed via photoisomerization of OClO to ClOO with subsequent decomposition of this species resulting in product formation. 4,12,28,29,[33][34][35][36] The gas-phase photochemical quantum yield for this process remains the subject of debate with values ranging from 0.15 to ∼0. 10,[15][16][17]20,21 In contrast, matrix isolation studies have demonstrated that photoexcitation of OClO results quantitatively in the formation of ClOO.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, intermolecular hydrogen bonding has been shown to play an important role in affecting the stability and reactivity of photoproducts in bulk liquids. 36 We and others have shown that solute-solvent hydrogen bonding can be significantly modified at interfaces, 37 contributing yet another factor that may affect photodissociation yield and dynamics.…”
Section: Introductionmentioning
confidence: 96%